Pengaruh Metode Sosiodrama Terhadap Kreativitas Belajar Siswa Kelas VIII SMP Negeri 3 Paranginan Kabupaten Humbang Hasundutan T.P 2024/2025 - Melpa Sintauli Hasibuan; Rida Gultom; Damayanti Nababan; Tiurma Barasa; Lasmaria Lumbantobing (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2025)
The purpose of this study was to determine the significant positive influence between the Sociodrama Method on the Creativity of Class VIII students of SMP Negeri 3 Paranginan, Humbang Hasundutan Regency, Academic Year 2024/2025. The method used in this study is a quantitative research method and the type of research is a pre-experimental design with the form of "One group pretest-posttest". The population is all students of class VIII of SMP Negeri 3 Paranginan who are Protestant Christians consisting of 2 classes totaling 47 people and a sample of 47 people was determined using the Nonprobability Sampling technique, namely Purposive Sampling. Data were collected with a closed questionnaire of 30 items. The results of the data analysis show that there is an influence of sociodrama on students' learning creativity as expected, as evidenced by the significant test obtained a calculated t value> t table (α = 0.05; dk = n-1 = 46) which is 9.524> 2.021, thus there is a significant influence between variable X and variable Y. Thus, H0 is rejected and Ha, namely there is a positive and significant influence between the Sociodrama Method on the Learning Creativity of Class VIII Students in the 2023/2024 Academic Year, is accepted.